Sharia Appraisal of the Bohe’ Ritual as a Way for Treatment and Prevention Disease - Arif Rahman Ramli; Muhammad Iqbal; Alfajri Anugrah (Pappaseng: International Journal of Islamic Literacy and Society, 2022)
Some residents of Bulukumba adhered to the bohe’ rite as a religious practice. The residents of Lembanna Village, Bontobahri District, Bukukumba Regency thought that the bohe’ ritual, in this case involving a walnut crab, possessed supernatural qualities and could cure a variety of illnesses. This study attempted to explain the ancestry of the bohe ceremony and evaluate Islam's approach to community rituals. This study employed a sociocultural, qualitative methodology. According to the research, bohe’ was an animistic ritual based on the ancestral practices of the inhabitants of Lembanna Village that was believed to be able to treat a variety of maladies, including skin diseases, itching, and allergies, and many people even asked for children. When one of the sick was immediately sent to bohe’ for a ritual to be performed in the hope that the ailment he experienced might be treated, the ritual became highly mystical in the community because it was a reference for previous individuals and a stigma for society. From the bohe’ ritual, it is possible to conclude that the rituals of the ancient people were not in accordance with the teachings of Islam, as the ritual process diverged from the religious faith, consisted of bad habits, and sought healing from a source other than Allah. In order to avoid deviating from the Islamic faith, it was hoped that the public would pay close attention to right and wrong and engage in a great deal of self-reflection by reading the prayers or mantras cast by Sanro (local shaman) or a handler with a more Islamic orientation, such as by reading shalawat or other suras from the Qur'an and Hadith.